VD_FINDINFO HC / 2011 / 679 vom 11. November 2011 - VD Tribunal cantonal (2011)
MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE, VENTE D'IMMEUBLE | 163 CC, 261 al. 1 CPC (CH), 276 al. 1 CPC (CH)